Polystyrene nanoplastics trigger pyroptosis in dopaminergic neurons through TSC2/TFEB-mediated disruption of autophagosome-lysosome fusion in Parkinson’s disease - Xiaomei Liang; Yaqi Zeng; Piao Zhang; Baoyu Zhu; Jiezhu Feng; Tongtong Deng; Zhongling Fu; Chengshuai Liu; Chengyu Chen; Yuhu Zhang (Journal of Translational Medicine)
Abstract Background Parkinson's disease (PD) is a sporadic neurodegenerative disorder with a rising incidence. Environmental toxins are considered the main etiological factor. The increasing use of polystyrene nanoparticles (PS-NPs) has raised concerns about their potential neurotoxic effects in PD. Objectives This study aimed to investigate the impact of PS-NPs on the onset and progression of PD and the underlying mechanisms. Methods The breach of the blood–brain barrier (BBB) by PS-NPs was assessed using bioluminescence imaging, fluorescence observation, Pyrolysis–Gas Chromatography-Mass Spectrometry (Py-GCMs), transmission electron microscope (TEM), and Evans blue staining. To evaluate the potential promotion of PD by PS-NPs, a 30-day repeated oral administration study was conducted in vivo, during which behavioral changes and alterations in dopaminergic neurons in the substantia nigra were assessed. In vitro cytotoxicity assays were performed following PS-NPs intervention. Molecular biology techniques, including Western blotting and immunofluorescence, were employed to analyze proteins related to pyroptosis and autophagy-lysosomal pathway in both in vivo and in vitro settings. Additionally, proteomic sequencing was utilized to identify the upstream regulator of the autophagy-lysosomal pathway (ALP), and the effects of modulating this target protein on the ALP-pyroptosis pathway were analyzed. Results Bioluminescence imaging and Py-GCMs confirmed that PS-NPs entered the brain within 1.5 h. Evans blue staining and TEM showed PS-NPs damaged the BBB. The 30-day oral toxicity revealed that PS-NPs exacerbated behavioral abnormalities and caused dopaminergic neuron loss. Western blotting and immunofluorescence indicated that PS-NPs induced pyroptosis, disrupted autophagic flux, and lowered protein levels involved in autophagosome-lysosome fusion, both in vivo and in vitro. Furthermore, PS-NPs activated the mechanistic target of rapamycin (mTOR) and inhibited the nuclear translocation of Transcription Factor EB (TFEB). Proteomic sequencing identified a deficit of Tuberous Sclerosis Complex (TSC) 2 protein within the mTOR pathway. Immuno-coprecipitation and Coomassie Blue Fast Staining revealed that PS-NPs bound to TSC2 protein, causing disassembly of TSC1-TSC2 complex. Conclusion These findings underscore how PS-NPs accelerated PD onset and progression by disrupting autophagosome-lysosome fusion through TSC2-mTOR-TFEB axis, which triggered protein degradation disorders and pyroptosis in dopaminergic neurons. The molecular mechanisms could inform environmental safety regulations concerning nanoplastics and inspire therapeutic strategies for PD. Graphical Abstract